2016
DOI: 10.1371/journal.pntd.0004788
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Variants of Rickettsia africae, and Incidental Identification of "Candidatus Rickettsia Moyalensis" in Kenya

Abstract: BackgroundRickettsia africae, the etiological agent of African tick bite fever, is widely distributed in sub-Saharan Africa. Contrary to reports of its homogeneity, a localized study in Asembo, Kenya recently reported high genetic diversity. The present study aims to elucidate the extent of this heterogeneity by examining archived Rickettsia africae DNA samples collected from different eco-regions of Kenya.MethodsTo evaluate their phylogenetic relationships, archived genomic DNA obtained from 57 ticks a priori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
6
10
0
Order By: Relevance
“…Analysis of tickborne zoonotic pathogens in this study corroborate findings of previous studies in Kenya, which have demonstrated circulation of zoonotic SFG Rickettsia in ticks from various ecologies [21,33,34). The presence of R. africae, which causes a potentially fatal, but as yet neglected febrile illness, was first reported in this ecosystem in 2003 [29].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Analysis of tickborne zoonotic pathogens in this study corroborate findings of previous studies in Kenya, which have demonstrated circulation of zoonotic SFG Rickettsia in ticks from various ecologies [21,33,34). The presence of R. africae, which causes a potentially fatal, but as yet neglected febrile illness, was first reported in this ecosystem in 2003 [29].…”
Section: Discussionsupporting
confidence: 88%
“…Previous reports have demonstrated high diversity of Rickettsia spp. and their potential vectors in Kenya [21,33,43]. Given that these reports have showed existence of novel species and uncharacterized variants of unknown pathogenicity, it will be important to undertake further studies of the unclassified Rickettsia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Rickettsia africae was detected in ticks collected from domestic animals and wildlife in Kenya at the Maasai Mara and the Shimba hill reserves ( Macaluso et al 2003 , Mwamuye et al 2016 ) and R. africae variants detected in ticks from rural Western Kenya. In a recent study, the heterogeneity of R. africae was confirmed and a new Rickettsia species identified that had been collected from the northern part of Kenya where communities are mainly nomads ( Kimita et al 2016 ). Nomadic communities in Kenya live in arid and semiarid zones and practice pastoralism with herds predominantly consisting of sheep, goats, and camels.…”
mentioning
confidence: 93%
“…A study conducted in Kenya by [63], reported that a partial fragment of ompB gene was found to be the most identical to Rickettsia rhipicephalus with 99.0% homology as against a required homology of 99.2% to qualify it as R. rhipicephalus, thus suggesting the probability of R. rhipicephalus circulating in African continent. Rhipicephalus spp.…”
Section: Discussionmentioning
confidence: 99%